2010
DOI: 10.1242/jeb.048181
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity and genetic adaptation to high-altitude hypoxia in vertebrates

Abstract: SummaryHigh-altitude environments provide ideal testing grounds for investigations of mechanism and process in physiological adaptation. In vertebrates, much of our understanding of the acclimatization response to high-altitude hypoxia derives from studies of animal species that are native to lowland environments. Such studies can indicate whether phenotypic plasticity will generally facilitate or impede adaptation to high altitude. Here, we review general mechanisms of physiological acclimatization and geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
343
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 353 publications
(382 citation statements)
references
References 178 publications
12
343
0
4
Order By: Relevance
“…In contrast, both Sherpas and Andean Quechuas show evidence for enhanced cardiac glucose uptake at the tissue level (50), and in Sherpas, the decreased ratio of phosphocreatine to ATP in cardiac myocytes suggests a greater reliance on glucose for ATP production (51). However, neither Quechuas nor Sherpas exhibit enhanced maximal aerobic capacities compared with lowlanders at similar fitness levels (52,53), suggesting that human patterns of metabolic adjustment may be optimized to enhance O 2 economy rather than maximal aerobic capacity (54).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, both Sherpas and Andean Quechuas show evidence for enhanced cardiac glucose uptake at the tissue level (50), and in Sherpas, the decreased ratio of phosphocreatine to ATP in cardiac myocytes suggests a greater reliance on glucose for ATP production (51). However, neither Quechuas nor Sherpas exhibit enhanced maximal aerobic capacities compared with lowlanders at similar fitness levels (52,53), suggesting that human patterns of metabolic adjustment may be optimized to enhance O 2 economy rather than maximal aerobic capacity (54).…”
Section: Discussionmentioning
confidence: 97%
“…Consideration of the joint effects of these co-varying environmental stressors should be a priority for future work (Altschuler and Dudley, 2006;Storz et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Tibetans differ from acclimatized lowlanders and other highaltitude human populations by maintaining sea-level hemoglobin (Hb) concentrations at elevations up to 4000 m (Beall et al, 1998;Beall, 2007). Although moderate increases in hematocrit and Hb concentration can improve aerobic capacity in normoxia (Ekblom and Hermansen, 1968;Kanstrup and Ekblom, 1984;Ekblom and Bergland, 1991), at high altitude, increased Hb concentration caused by excessive erythrocytosis can hinder tissue oxygenation by increasing blood viscosity and vascular resistance (Guyton and Richardson, 1961;Connes et al, 2006;Storz et al, 2010b). Correspondingly, theoretical studies have suggested that optimal Hb concentrations may be near the typical sea-level value (Villafuerte et al, 2004).…”
Section: Genomic Approaches To the Study Of High-altitude Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Body plasticity implies the body responds to the environmental demands placed on it by continually modifying itself to better match environmental changes, [137]- [139].…”
Section: Epigenetic Plasticitymentioning
confidence: 99%